The Effect of a Growth Mindset on the Chemistry Learning Process Among 11th-Grade Students in Class XI-P2 at SMAS Bhaktyarsa Maumere in 2024 - Jose Glorio Sufa; Edmund Chayono Moa; Petrus Afendi (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze the tendency of growth mindset and fixed mindset and their relationship with the chemistry learning process in the perspective of educational psychology. The research used a mixed method approach, namely a descriptive quantitative and qualitative approach with a total sampling technique for 34 students of SMAS Bhaktyarsa Maumere. The instrument used was a Likert scale-based mindset questionnaire that has been tested for validity and reliability. Data analysis was carried out through simple descriptive and correlational statistics. The results showed that 55.9% of students were in the fixed mindset category and 44.1% in the growth mindset category. The validity test showed most of the instrument items were feasible for use in the study, while reliability was in the category of sufficient. The findings indicate a tendency to have a positive relationship between growth mindsets and the quality of the chemistry learning process, especially in the aspects of perseverance, response to difficulties, and learning motivation. However, the strength of the relationship obtained in this study has not fully demonstrated a causally significant influence, so further research with a stronger inferential design is needed.